Population Decline May Affect the Incidence of Pulmonary Tuberculosis in Japan - Akihiro Miyauchi; Mizuki Inaba; Takatoshi Tetsuka; Noritaka Sakamoto; Yushi Nomura; Otohiro Katsube; Hirokuni Hirata; Hiroshige Yoshioka; Seiji Niho; Kumiya Sugiyama (Journal of Clinical Medicine, 2026)
Background/Objectives: Pulmonary tuberculosis in Japan had been decreasing as a result of the country’s anti-tuberculosis policy. The decreased number of patients with tuberculosis has led to many tuberculosis units being downsized. However, the decreasing trend in incidence ended in 2022. To resume this trend, it is important to clarify which populations are at higher risk of developing tuberculosis. Methods: This study analyzed annual reports on tuberculosis published by the Japanese government from 2015 to 2024. Results: Among Japanese nationals, the number of newly notified cases of tuberculosis had been decreasing in all age groups. However, the number of newly notified cases among foreign-born residents has sharply increased since 2022, and the rate of newly notified cases among foreign-born residents per 100,000 population was highest in the 20–39-year age group. During the observation period, the number of foreign-born workers from countries with a high incidence of tuberculosis had increased, and the populations of several countries and the corresponding numbers of tuberculosis notifications increased. Conclusions: This study revealed that younger foreign workers from those countries are more likely to develop pulmonary tuberculosis in Japan. The change in population composition may have impacted the incidence of tuberculosis in Japan and will be a hindrance to efforts to decrease the number of tuberculosis cases going forward. Therefore, more effective pre-entry tuberculosis screening should be introduced for young migrant workers from countries with a high incidence of tuberculosis cases.